Physiological alterations in the oral microbiome: A scoping review - Ohara, Masaru; Puteri, Mega Moeharyono; Kagami, Hideaki; Kazaoka, Yoshiaki; Saskianti, Tania (Dental Journal (Majalah Kedokteran Gigi), 2026)
Background: The oral cavity contains more than 774 species of microorganisms, which are collectively referred to as the oral microbiome. Oral microorganisms and their hosts maintain harmonious relations to coexist. Although there are many reviews on the relationship between oral diseases and oral microbiome composition, few articles describe the timing and causes of alterations in the oral microbiome of healthy individuals, particularly those due to lifestyle changes. Purpose: This review aims to identify factors related to physiological alterations in the oral microbiome of healthy individuals due to lifestyle changes, excluding disease-associated dysbiosis. Review: A literature search was performed using PubMed, Latin American and Caribbean Health Sciences Literature, Scientific Electronic Library Online, and Wiley online databases for the period of 2014–2024. Using the keywords ([oral microbiome change] AND [oral microbiome alteration]) AND (geographic, ethnic, culture, or lifestyle), 17 articles matched the inclusion and exclusion criteria for this study. Physiological microbiome alterations were categorized into three groups: (a) the historical change of the oral microbiome from ancient to modern lifestyles, (b) the dynamics of the oral microbiome over short periods due to current lifestyle changes, and (c) oral microbiome alterations during developmental stages. Conclusion: This review identified representative factors related to physiological alterations in the oral microbiome, including ancient–modern lifestyle changes, immigration, and childhood development. These three factors may assist physicians in distinguishing between dysbiosis and physiological change. Because time-course study designs make it easier to understand individual changes, researchers recommend utilizing longitudinal study methods.